Ekspektasi Biaya Kerugian Kualitas Produk Triplex 3 mm Dengan Pendekatan Model Fungsi Kuadrat Simetris - J. M. Tupan (ARIKA, 2011)
Deviation length, width and thickness of the nominal value / target value specified indicates the variation of process and product. Deviations may occur in the range of specification limits and outside the specification limits and the impact on cost and quality of product produced. This study aims to determine variations in the size dimension Triplex products sold in the city of Ambon is in or outside the specification limits (tolerances) are defined and calculated expectations of quality loss incurred by consumers. The analysis showed that the products sold Triplex has a variety of dimensions length, width and thickness below the lower specification limit or above the upper specification limit. Expectations of average quality loss - Average per unit (pieces) are borne by the consumer for a long dimension triplex between Rp. 0.2026 s / d Rp. 0.4051; for triplex width dimensions ranging from Rp. 4.6902 s / d Rp. 9.3804 and for the dimensions of thick triplex between Rp. 1.0144 s / d Rp. 2.0289. With expectations for quality losses is Rp. 677,328.28.